Meaning structure and dialectal features in the speech of the Ngatag tradition in Bugbug village, Karangasem, Bali - Ni Komang Aryani; Suwarna Dwijonagoro (LITERA, 2026)
Oral tradition, as part of local culture, plays an important role in sustaining the social and customary values of society. However, its linguistic practices remain understudied, particularly in terms of meaning and dialectal variation. This study aims to analyze the lexical meaning, conceptual meaning, and dialectal features in the speech of the Ngatag tradition in Bugbug Village, Karangasem, Bali. The Ngatag tradition is a customary oral communication practice used to convey information about the implementation of Sangkepan Desa (customary village meetings) while affirming the community’s collective obligations. This study employs a dialectological approach with semantic analysis. The data consist of Ngatag utterances delivered by Kasinoman to Krama Ngarep, collected through observation, documentation, and in-depth interviews, then verified through source and method triangulation. The findings show that, lexically, Ngatag utterances consist of territorial markers, time markers, conditional structures, and consequences. Conceptually, these utterances contain meanings of participatory invitation, affirmation of social obligation, and legitimation of customary norms. In addition, Ngatag utterances exhibit Bugbug dialectal features through the retention of the final vowel /a/, the use of local vocabulary, and firm syntactic structures. Thus, Ngatag functions not only as a medium of information but also as a representation of the linguistic and cultural identity of the Bugbug community.